Scenarios for health expenditure in Poland - Stanisława Golinowska; Ewa Kocot; Agnieszka Sowa (Center for Social and Economic Research (CASE), 2008)
The report is a result of the Ageing, Health Status and Determinants of Health Expenditure (AHEAD) project within the EC 6th Framework programme. The objective of the research was to present the model of future health care system revenues and expenditures in Poland and to discuss projection assumptions and results. The projections are based on methodology adopted in the International Labour Organization (ILO) Social Budget model. The projection examines impact of demographic changes and changes in health status on future (up to 2050) health expenditures. Next to it, future changes in the labour market participation and their impact on the health care system revenues are examined. Impact of demography on the health care system financial balanced is examined in four different scenarios: baseline scenario, death-related costs scenario, different longevity scenario and diversified employment rates scenario. Results indicate dynamic and systematic increase of the health expenditures in the next 30 years. Afterwards the dynamics of this process is foreseen to slow down. Despite the increase of the revenues of the health care system, the system will face deficit in the close future. This holds for each scenario, however the size of the deficit differs depending on longevity and labour market participation assumptions. Results lead to a discussion on possible reforms of the health care system.
Keywords: H51; 330; health care system; demographic projection; health care system revenues and expenditures projection; Poland; Gesundheitsökonomik; Gesundheitsfinanzierung; Gesundheitskosten; Prognose; Bevölkerungsprognose; Gesundheitsreform; Polen